Ethanol extract of mangosteen (Garcinia Mangostana Linn) peel effect in inhibiting the growth of human tongue cancer cells Supri’s Clone 1, invitro - Suanto, Edi; Oewen, Roosje Rosita; Sasmita, Inne Suherna; Supriatno, S.; Supratman, Unang (Universitas Padjadjaran, 2011)
The incidence of tongue cancer in Indonesia reached 1.01% of all cancers and 42% of oral cavity cancer. Tongue cancer therapies including chemotherapy, radiotherapy, surgery, and all three combined therapy. Search for anti-cancer drugs currently switched on herbal plants, one of which is the mangosteen. Has the properties of mangosteen peel extract inhibited the growth of cancer cells. The purpose of the study, obtain IC50 of ethanol extract of mangosteen peel in inhibiting the growth of human tongue cancer cells SP-C1. Research carried out on 96 preparations of human tongue cancer SP-C1 were incubated with ethanol extract of mangosteen peel, preparations were classified in two groups of incubation time (24 hours and 48 hours) and each group will be given preferential treatment over 6 randomly different concentrations: 0 (control), 62.5 μg/mL, 125 μg/mL, 250 μg/mL, 500 μg/mL and 1000 μg/mL. Model experiments were 2 x 6 factorial experiment with eight replication for each cell. Test results with ANAVA, incubation (24 and 48 hour) SP-tongue cancer cells with various concentrations of C1 ethanol extract of mangosteen peel gives a highly significant, indicating differences cancer cell growth inhibition. Incubation time factor showed the long incubation effect on cancer cell growth inhibition. Furthermore, by Newman Keuls test, showed 500μg/mL concentrations of 24-hour incubation had the best effect. Conclusion of the study of ethanol extract of mangosteen peel could achieve with IC50 values of cell growth resistance 50.3% at a concentration of 500 μg/mL and an incubation time of 24 hours.